The limitations of applying zero-valent iron technology in contaminants sequestration and the corresponding countermeasures: The development in zero-valent iron technology in the last two decades (1994–2014). (15th May 2015) - Guan, Xiaohong; Sun, Yuankui; Qin, Hejie; Li, Jinxiang; Lo, Irene M.C.; He, Di; Dong, Haoran
Abstract: Over the past 20 years, zero-valent iron (ZVI) has been extensively applied for the remediation/treatment of groundwater and wastewater contaminated with various organic and inorganic pollutants. Based on the intrinsic properties of ZVI and the reactions that occur in the process of contaminants sequestration by ZVI, this review summarizes the limitations of ZVI technology and the countermeasures developed in the past two decades (1994–2014). The major limitations of ZVI include low reactivity due to its intrinsic passive layer, narrow working pH, reactivity loss with time due to the precipitation of metal hydroxides and metal carbonates, low selectivity for the target contaminant especially under oxic conditions, limited efficacy for treatment of some refractory contaminants and passivity of ZVI arising from certain contaminants. The countermeasures can be divided into seven categories: pretreatment of pristine ZVI to remove passive layer, fabrication of nano-sized ZVI to increase the surface area, synthesis of ZVI-based bimetals taking advantage of the catalytic ability of the noble metal, employing physical methods to enhance the performance of ZVI, coupling ZVI with other adsorptive materials and chemically enhanced ZVI technology, as well as methods to recover the reactivity of aged ZVI. The key to improving the rate of contaminants removal by ZVI and broadening the applicable pH range is to enhance ZVI corrosion and to enhance the mass transfer of the reactants including oxygen and H + to the ZVI surface. The characteristics of the ideal technology are proposed and the future research needs for ZVI technology are suggested accordingly. Graphical abstract: Highlights: The development of ZVI-based technologies in the past two decades was reviewed. The limitations of ZVI technology and the countermeasures were summarized. The merits and demerits of each countermeasure were discussed in detail. The future research needs in the field of ZVI technology were suggested. The characteristics of an ideal ZVI technology were proposed.